2003
DOI: 10.1542/peds.112.5.1054
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Procalcitonin and C-Reactive Protein Tests in Children With Fever Without Localizing Signs of Infection Seen in a Referral Center

Abstract: PCT and CRP performed better than IL-6, WBC, and/or band count in predicting the occurrence of SBI. PCT and CRP bedside tests may be useful tools for emergency and private practice doctors and should be considered in the initial work-up of children with fever without source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
136
4
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(165 citation statements)
references
References 34 publications
14
136
4
11
Order By: Relevance
“…This is higher in infants aged 0-28 days (9-28%) than those 2-3 months old (7.1%) [2][3][4][5][6][7][8][9]15,16]. We found the overall rate of SBI was high (38.4%) and our findings confirmed that SBI was seen more frequent in the neonatal period.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is higher in infants aged 0-28 days (9-28%) than those 2-3 months old (7.1%) [2][3][4][5][6][7][8][9]15,16]. We found the overall rate of SBI was high (38.4%) and our findings confirmed that SBI was seen more frequent in the neonatal period.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, UTI was found higher and reported that 14-21.3 percent in febrile neonatesthat means UTI affects approximately 1 in 6 febrile neonates [2][3][4][5][6][7][8][9][10][11]18]. In our study, UTI incidence was found similarly the most common etiology of fever in neonatal period.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The prevalence of SBI in our study was 26.2% (39 out of 149 patients were positive for serious bacterial infection), Allen L. Hsiao et al (2) studied 429 infants out of which 44 (10.3%) patients were diagnosed with serious bacterial infection, in another study Pulliam PN et al (16) studied seventy-seven patients and they enrolled SBI in 18% of the patients and Annick Galetto-Lacour et al (17) studied 99 patients and noticed serious bacterial infection in 29%.…”
Section: Discussionsupporting
confidence: 44%
“…dem CRP. Umgekehrt besitzt PCT einen hohen negativen pr ä diktiven Wert, d.h. niedrige PCT-Konzentrationen schlie ß en eine Infektion mit hoher Wahrscheinlichkeit aus [19,25] . So wurde zum Ausschluss einer Sepsis f ü r PCT bei einem Cut-Off von 0,2 ng/mL ein negativer pr ä-diktiver Wert von 99 % beschrieben [111] .…”
Section: Therapiesteuerungunclassified